A Comparative Study of Students’ Stress Levels when Assessed through Summative Assessment versus Outcome-Based Assessment in an Elementary Chinese Course - Inplaeng, Thirayu (Journal of Education Studies, Chulalongkorn University, 2024)
This research aimed to (1) study the current state and needs of an elementary Chinese course assessment method, (2) compare the stress levels of students who received summative assessments with those who received outcome-based assessment, and (3) provide recommendations for learning assessment. The research sample consisted of 144 students majoring in Teaching Chinese Language School of Sinology Mae Fah Luang University, selected through sample size determination and simple random sampling. The research instruments included: (1) a questionnaire on the current state and needs of the course, (2) course assessment tools, (3) the Suanprung Stress Test, and (4) a focus group discussion record. This research employed a experimental research design to study need with PNImodified and compare the stress scores between students who received summative assessment and those who received outcome-based assessment. Descriptive statistics and the t-test were used for data analysis. The research findings were as follows: (1) The study of the current stage and needs assessment reveal that students exhibit proficiency in classical test methods, such as summative assessments using various types of tests. Overall, no significant issues were found regarding evaluation and measurement in introductory Chinese language courses. Additionally, students expressed a high necessity for receiving feedback. (2) The comparison results of stress scores indicate that the stress levels of research samples studying Chinese food, beverages, desserts, Chinese traditions and culture in the group assessed by outcome-based learning evaluation were significantly lower than those in the group assessed by summative learning evaluation at the .05 level of statistical significance. In contrast, the stress levels of research samples studying Chinese directions and tourist attractions were significantly lower in the group assessed by summative learning evaluation compared to the group assessed by outcome-based learning evaluation at the .05 level of statistical significance. (3) Recommendations for improving the learning assessment process included the format of tests, assessment criteria, and the weighting of scores.